Optimization of Bacillus subtilis NRC1 growth conditions using response surface methodology for sustainable biosynthesis of gold nanoparticles - Magda A. El-Bendary; Salwa S. Afifi; Maysa E. Moharam; Mostafa M. Abo Elsoud; Noha A. Gawdat (Scientific Reports, 2022)
Abstract Gold nanoparticles (AuNPs) have different unique properties and a wide range of applications in different fields. Thereby, there is a growing urgency for the production of AuNPs using a safe and an economic method. In this study, optimization of fermentation conditions by Bacillus subtilis NRC1 for extracellular AuNPs synthesis using response surface methodology was achieved. The data obtained from Plackett–Burman design followed by Box–Behnken design indicated the accuracy and reliability of the model and it could be used to navigate the design space with a reasonable accuracy. Numerical optimization of Bacillus subtilis NRC1 active extracellular filtrate production, showed the optimum conditions of 0.74% (w/v) casein hydrolysate, 3.99% (w/v) dextrin, 47 × 106 CFU/ml inoculum size at pH 7.76 and 25 $$^°$$ ∘ C to give the maximum AuNPs biosynthesis. The model was highly valid and the obtained data had a confidence factor of 98.48%. Statistical optimization resulted in a 2.6-fold increase in AuNPs production compared with that of the non-optimized medium.